Guidance Note on the New Design for Article IV Consultation Reports. (Policy Papers; Policy Paper ;, 2011)
Earlier in 2011, Management approved a new design covering both the design and structure for stand-alone Article IV staff reports. All stand-alone Article IV reports issued to the Board after September 1 are being prepared in the new format. It is anticipated that this new design will be rolled out gradually over the course of the next fiscal year for other country reports and policy documents.